Národní registr endoprotéz kyčelního kloubu jako zrcadlo léčby vývojové dysplazie kyčle u novorozenců - Zídka, M; Džupa, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2019)
PURPOSE OF THE STUDY In the Czech Republic a systematic neonatal hip screening has been performed for many decades. Its aim is to prevent, by means of early treatment of hip dysplasia in the newborn period, the development of hip deformities leading to the onset of degenerative hip changes during the adulthood. The study aims to prove the effects of paediatric hip care based on the data analysis of the Czech National Register of Joint Replacement. MATERIAL AND METHODS The National Register of Joint Replacement comprises information on implantation of hip arthroplasties performed over the period of last 15 years, while the screening has been carried out for almost 60 years. An analysis of the patients' data from the register was conducted; the data was sorted by the diagnosis leading to surgery in individual age categories and individual years. The obtained data was correlated with the systems of newborn hip screening at the time when the treated generations of patients were born. RESULTS According to the National Register of Joint Replacement, in the period 2003-2017 a total of 174,515 primary hip joint replacements were performed, 345 total hip arthroplasties (0.19 %) were implanted for complete hip dislocation in dysplasia, 14,139 replacements (8.10%) were performed for postdysplastic hip degeneration. By comparing the periods 2005-2007 and 2015-2017 a decrease almost to a half of the number of implanted endoprostheses for hip dislocation was identified. Moreover, only 8 of 345 dislocated hips in the Register were managed by joint replacement in patients who were born during the systematic screening period. The percentage of endoprostheses implanted for postdysplastic degeneration decreased respectively; in 2005-2007 period 2,692 of 28,525 hip endoprotheses (9.44%) were implanted, whereas in 2015-2017 period 3,285 of 46,228 hips (7.11%) were operated on. This decline is statistically significant (p < 0.001, OR 1.34). DISCUSSION The efficiency and success rate of sonography resulted in Central Europe in such a rapid expansion of neonatal ultrasound hip screening that no comparative studies were carried out to confirm this concept (as is currently requested by evidencebased-medicine). This has later become the source of misunderstanding and subject to criticism primarily in the overseas literature. Those who focus on ultrasound screening feel that conducting prospective randomised studies on (non)treatment in ultrasound detected pathologies is ethically unacceptable today. When seeking another way of confirming the efficiency of universal screening, a detailed analysis of data from the hip joint replacement registry has proven successful. CONCLUSIONS A low number of arthroplasties implanted for hip dislocation in the Czech population is recorded in the National Register of Joint Replacement. This confirms the success of the existing system of neonatal hip screening; the results show that the treatment of hip dislocation in children is successful. The ongoing decline in the share of patients in the population treated by total hip replacement in postdysplastic degeneration has been confirmed. Data evolution will be subject to further research in the upcoming decades, with a positive effect of ultrasound monitoring of treatment to be foreseen. Key words: developmental dysplasia of the hip, screening, register of joint replacements.
Keywords: Registries; novorozenec; Infant, Newborn; Humans; vývojová kyčelní dysplazie; dítě; registrace; Child; Arthroplasty, Replacement, Hip; dospělí; Ultrasonography; náhrada kyčelního kloubu; lidé; Adult; ultrasonografie; Czech Republic; Mass Screening; Hip Dislocation, Congenital; plošný screening; Česká republika; prospektivní studie; Prospective Studies